The Trendermarsch sunken in the Wadden Sea (North Frisia, Germany) – reconstructing a drowned medieval cultural landscape with geoarchaeological and geophysical investigations - A. Reiß; H. Hadler; D. Wilken; B. S. Majchczack; R. Blankenfeldt; S. Bäumler; U. Ickerodt; S. Klooß; T. Willershäuser; W. Rabbel; A. Vött (Eiszeitalter und Gegenwart, 2025)
Located in the North Frisian Wadden Sea, today's tidal flat sediments cover a formerly cultivated area outside the present-day sea dike of Nordstrand that had been occupied by settlers since the Middle Ages. The intensive cultivation increased the coast's vulnerability to storm floods. Especially the medieval storm surges of the first Grote Mandränke (St Marcellus flood) in 1362 CE and the second Grote Mandränke (Burchardi flood) in 1634 CE destroyed large parts of the diked marshland.